Trade-Offs? The Impact of WTO Accession on Intimate Partner Violence in Cambodia - Bilge Erten; Pinar Keskin (Institute of Labor Economics (IZA), 2021)
We study the impact of trade-induced changes in labor market conditions on violence within the household. We exploit the local labor demand shocks generated by Cambodia's WTO accession to assess how changes in the employment of women relative to men affected the risk of intimate partner violence. We document that men indistricts facing larger tariff reductions experienced a significant decline in paid employment, whereas women in harder-hit districts increased their entry into the laborforce. These changes in employment patterns triggered backlash effects by increasing intimate partner violence, without changes in marriage, fertility, psychological distress, or household consumption.
Keywords: F16; O15; J12; J16; 330; trade; intimate partner violence; employment; marriage; fertility; consumption; Cambodia